Calculation of fully relativistic cross sections for electron excitation of cesium atom and its application to the diagnostics of hydrogen-cesium plasma. (January 2017) - Priti,; Dipti,; Gangwar, R.K.; Srivastava, R.
Abstract: Electron impact excitation cross-sections and rate coefficients have been calculated using fully relativistic distorted wave theory for several fine-structure transitions from the ground as well as excited states of cesium atom in the wide range of incident electron energy. These processes play dominant role in low pressure hydrogen-cesium plasma, which is relevant to the negative ion based neutral beam injectors for the ITER project. As an application, the calculated detailed cross-sections are used to construct a reliable collisional radiative (CR) model to characterize the hydrogen-cesium plasma. Other processes such as radiative population transfer, electron impact ionization and mutual neutralization of Cs + ion with negative hydrogen ion along with their reverse processes are also taken into account. The calculated cross-sections and the extracted plasma parameters from the present model are compared with the available experimental and theoretical results. Highlights: Relativistic distorted wave theory is used to calculate the electron-impact excitation of cesium . Electron impact excitation rate-coefficients are calculated as a function of electron temperature . A collisional radiative (CR) model has been developed using the obtained cross-sections and the characterization of the hydrogen-cesium plasma has been done .